Ruang Virtual : Wujud Kreativitas Digital di Ruang Publik - Isfiaty, Tiara; Saleh, Adzkay Dani (Waca Cipta Ruang, 2023)
Virtual space is a movement in spatial creation. Digital technology is employed in virtual space to give users the chance to engage in certain activities with the goal of having a unique experience from that of conventional space. In contrast to typical venues, this encounter offers a unique spatial experience. The goal of this research is to develop an alternative to creating virtual environments based on factors that can affect a person's decision to adopt or reject an invention. Aim of the study is to develop an alternative to building virtual environments based on factors that can affect a person's decision to adopt or reject an innovation. This study seeks to (a) determine the features of space user behaviors when participating in audio-visual media based on digital technology ((b) analyze the perceptions created by users of public spaces. According to the study's goals, which center on comprehending the experience of a digital world, it employs qualitative research techniques. The study's findings revealed that (a) audio-visual material based on digital technology effects users' activity patterns, including how often and how long they sit in digital spaces. (b) the interaction between participants and attractiveness in digital media and space users changes their conceptions of the purpose of public space.